Board leadership in global ventures: A bibliometric analysis - Herrera-Barriga, Roberto Andres (2024)
This study explores the relationship between administrative advice and international market entry modes. The board of directors has the authority to determine internationalization strategies for both large multinational corporations and small and medium-sized organizations. Existing theoretical frameworks dealing with internationalization provide a strong foundation for understanding the dynamics of entry modes and corporate governance. The study presents a framework consisting of four thematic elements: characteristics, capabilities, behavior, and composition of the advice. This framework is utilized to analyze the complexities of the decision-making processes of boards. Despite acknowledging its limitations, this study provides practical insights for business managers and contributes to the ongoing theoretical debate on this topic, highlighting the need for more comprehensive frameworks that consider psychological and cultural factors in the decision-making process of boards in the context of international business.